Analysis of Follower Satisfaction on The Instagram Account @infokonser - Samatan, Nuriyati; Syas, Mulharnetti; Robingah, Robingah; Aladdin, Yuri Alfrin; Gemilang, Rattu (International Journal of Advanced Multidisciplinary, 2025)
Research Objective: This study aims to analyze follower satisfaction on the @infokonser account through three variables: social media and information quality variables as X1 and X2; and information fulfillment variable as Y. Research Method: the type of research is quantitative, the paradigm used is positivism,The sampling technique used is non-probability sampling, the sample determination uses purposive sampling, while the sample size determination uses the Slovin formula with a margin of error of 0.5% with a total of 400 respondents.The questionnaire was distributed via Google Forms to the followers of the Instagram account @infokonser.Analysis was conducted using SPSS version 29. Findings: this study found that, partially, there is an influence of the @infokonser social media on the fulfillment of followers' information, and there is an influence of the quality of @infokonser information on the fulfillment of followers' information; and simultaneously, the social media variable and the quality of @infokonser information together influence the information needs of followers.